Nilai-Nilai Spiritual Dan Identitas Budaya Aceh Dalam Tari Saman - Muslem Ilyas; Tuhfatul Athal (International Forum of Researchers and Lecturers, 2025)
Islam entered and spread in Aceh in very fascinating and respectful manner. The previous preachers had created an extraordinary creativity in integrating Islamic teachings with Acehnese culture, making it widely accepted. This research aims to analyze the spiritual values that have merged with Acehnese culture in the Saman Dance, as well as analyze the meaning of the lyrics and movements in the Saman Dance that related to spiritual values. The data for this research was collected through library research using a qualitative approach. The analysis results indicate that the Saman Dance, as an expression of Acehnese culture, has successfully acculturated spiritual Islamic values with the local culture in a harmonious way. This is reflected in the movements and lyrics used in the dance, which convey Islamic spiritual values. The Saman Dance is not only an art form aimed at entertainment, but also serves as a medium to convey Islamic preachings messages.